تأثير معدلات مختلفة من الأسمدة الآزوتية والفوسفورية والبوتاسية في نمو وإثمار أشجار الأكيدنيا - خربوتلي, رشيد (Latakia University Journal -Biological Sciences Series, 2018)
يهدف البحث إلى تحديد الكمية المثلى من الأسمدة الكيماوية لأشجار الأكيدنيا "الصنف الصيداوي" في طور الإثمار والمطعمة على الأصل البذري للأكيدنيا، وقد استخدمت عدة معاملات سمادية وأظهرت الدراسة النتائج التالية: 1- وجود تأثير إيجابي للتسميد الكيماوي في جميع الصفات الخضرية والثمرية المدروسة لأشجار الأكيدنيا مقارنة مع معاملة الشاهد. 2- أعطت المعاملة السمادية التالية: - 400 غ آزوت نقي للشجرة (N). - 240 غ فوسفور نقي للشجرة (P2O5). - 240 غ بوتاس نقي للشجرة (K2O). أفضل نمو خضري وأكبر إنتاج ثمري لأشجار الأكيدنيا بالمقارنة مع باقي المعاملات السمادية المختارة. In order to determine the optimal quantity of chemical fertilizers of loquat trees at the fruiting stages, several fertilizing treatments were used. The study on the sedawi variety transplanted on wild origin of loquat showed the followings: 1- A positive effect of the chemical fertilizer on all vegetative and fruiting features studied compared to the control. 2- The following fertilizer equation (400g N, 240g P2O5 and 240g K2O per tree) gave the best vegetative growth and the largest fruit production on loquat tree compared to the remaining fertilizer treatments.